Use of lidocaine to prevent postoperative coughing after partial laryngectomy: comparison of three delivery methods - Wang Y; Lu WS; Qiao H; Zhao J; Fan Q (Dove Medical Press, 2019)
Yuezhi Wang,1,* Wei S Lu,2,* Hui Qiao,2 Jian Zhao,3 Qing Fan21Department of Gerontology, Huashan Hospital of Fudan University, Shanghai 200040, People’s Republic of China; 2Department of Anesthesiology, The Eye, Ear, Nose and Throat Hospital of Fudan University, Shanghai 200031, People’s Republic of China; 3Department of Gerontology, Shanghai Sixth People’s Hospital Jinshan Branch, Shanghai, 201500, People’s Republic of China*These authors contributed equally to this workObjective: To compare the effectiveness of lidocaine administration (intravenous injection, dripping via the tracheostomy tube, and spraying into the tracheostomy incision) on postoperative coughing after partial laryngectomy.Patients and methods: A total of 115 male patients with laryngeal carcinoma scheduled for partial laryngectomy under general anesthesia were randomized into three groups. In group I (n=35), 2% lidocaine hydrochloride (1.5 mg/kg) was slowly infused intravenously. In group II (n=40), 2% lidocaine hydrochloride (1.5 mg/kg) was dripped into the tracheostomy tube upon completion of surgery. In group III (n=40), 7% lidocaine aerosol (5 sprays, 22.5mg) was sprayed into the tracheostomy incision before tracheostomy tube placement. We recorded incidences of coughing, incisional bleeding, and hemodynamic changes when leaving the postanesthesia care unit (T1), and 6 hrs (T2) and 24 hrs (T3) after surgery.Results: The coughing scores and incisional bleeding scores were significantly lower in group II and III than that in group I at T1, T2, and T3. Group II and III had significantly lower heart rate than group I at T1 and T2. Compared with group I, mean arterial pressure decreased significantly in group II (T1 and T2) and group III (T1 and T3).Conclusion: In patients undergoing partial laryngectomy, spraying 7% lidocaine aerosol into the tracheostomy incision before placing the tracheostomy tube or instilling 2% lidocaine hydrochloride into the tracheostomy tube upon completion of surgery effectively prevented postoperative coughing, which reduced the risk of bleeding from the incision and thus facilitates postoperative rehabilitation.Keywords: lidocaine, laryngeal carcinoma, partial laryngectomy, postoperative bucking